Pendidikan Inklusif dalam Perspektif Teologi Kristen : Peluang dan Tantangan - Dwi Rizka Agustina; Retna Tri Hastuti; Deni Candra Saputra (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2024)
This article explores the concept of inclusive education from a Christian theological perspective, which emphasizes acceptance and love for all individuals without discrimination. This study analyzes how Christian values ​​can be applied in an inclusive educational environment, especially for students with special needs. The results of the study indicate that a Christian theological-based approach can create a culture of inclusion that strengthens solidarity and equality. This article also discusses the challenges of implementing inclusive education and offers practical solutions for educators.